Enhancing Learning Performance in Primary Education: The Roles of Problem Solving and Creative Thinking Challenges - Nguyen, Pham Ngoc Thien; Tran, Khanh-Trinh; Buu Le, Giam (Revija za elementarno izobraževanje, 2025)
This study investigated the roles of problem-solving and creative thinking activities in primary science education. Participants included 64 third-grade and 62 fifth-grade students in Southern Vietnam, with half assigned to experimental groups and the others to control groups. The experimental groups, which received structured lessons, outperformed the control groups, which received traditional instruction. Results highlight the positive impact of integrating these activities on academic performance, supporting the effectiveness of structured support in enhancing learning outcomes.